(untitled) (Contemporary Issues on Indonesian Human Rights Law and Policy, 2024)
This paper analyzes the human rights situation in Indonesia’s conflict zones, focusing on Aceh and Papua, where ongoing or historical military presence has often been associated with human rights abuses. Drawing on fieldwork, interviews with victims, and reports from human rights organizations, the study investigates the extent of abuses such as extrajudicial killings, torture, forced displacement, and restrictions on freedom of expression. The research highlights the correlation between military operations and the deterioration of civil rights in these regions. The paper also discusses the challenges to achieving justice for victims, including weak accountability mechanisms and impunity. The findings suggest that while Indonesia has made progress in addressing past abuses, the persistence of military influence in these areas continues to pose significant human rights challenges. This paper offers a critical evaluation of the impact of military presence on human rights, providing a comprehensive case study of Aceh and Papua to illuminate broader patterns of abuse in conflict zones. By focusing on the role of military presence in human rights violations, the paper contributes to the literature on conflict, military accountability, and human rights, with specific relevance to Southeast Asia.